2022
DOI: 10.1101/2022.01.31.478542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human immunodeficiency virus type 2 capsid protein mutagenesis reveals amino acid residues important for virus particle assembly

Abstract: Human immunodeficiency virus (HIV) Gag drives particle assembly. The capsid (CA) domain is critical for Gag oligomerization, and encodes key residues that dictate Gag-Gag interactions and particle morphology. The immature particle morphology of HIV-2 is intriguing different relative to that of HIV-1. To help define the critical determinants for Gag-Gag interactions and investigate the differences between HIV-1 and HIV-2, we have conducted mutagenesis in targeted locations of HIV-2 CA that have been implicated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…HIV-2 CA G38M and HIV-1 CA M39G reduced virus particle production by 50%, and eliminated virus infectivity. The HIV-2 CA N127E mutant, which swaps HIV-1 and HIV-2 residue identity, severely reduced particle production [34]. In addition, HIV-2 is insensitive to the HIV-1 maturation inhibitor (MI) Bevirimat (BVM) [35].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-2 CA G38M and HIV-1 CA M39G reduced virus particle production by 50%, and eliminated virus infectivity. The HIV-2 CA N127E mutant, which swaps HIV-1 and HIV-2 residue identity, severely reduced particle production [34]. In addition, HIV-2 is insensitive to the HIV-1 maturation inhibitor (MI) Bevirimat (BVM) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, the CTD of CA is important for both the formation of the core in mature particles and in virion assembly in immature particles [ 72 ]. In all retroviruses, a conserved sequence known as the major homology region (MHR) is located in the CTD of the precursor PR55 Gag CA [ 73 ]. The entire MHR region forms a compacted strand–turn–helix stabilized by a network of salt bridges and hydrogen bonds [ 74 ].…”
Section: Capsidmentioning
confidence: 99%
“…While the structural determinants of HIV-1 Gag oligomerization have been extensively studied in authentic particles (114)(115)(116), virus-like particles (117)(118)(119), and in vitro assemblies of purified CA proteins (120), high resolution of the structure of the HTLV-1 has been limited to nuclear magnetic resonance (NMR) studies of the HTLV-1 CA domain (121). Comparative studies probing residues within CA have identified many of the key interaction interfaces required for maintaining replication and morphology of HIV-1 (122,123), HIV-2 (124), and HTLV-1 (81), including those that dictate the formation of structural features such as the six-helix bundle of CA-SP1 and the two-and three-fold CA interfaces. Recent determination of the structure of the HIV-2 immature lattice demonstrates a similar hexameric organization to that of HIV-1 (125), further emphasizing the unique nature of HTLV-1 among human retroviruses.…”
Section: Morphological Diversity In Human Retrovirus Particlesmentioning
confidence: 99%